2001
DOI: 10.1038/sj.gt.3301433
|View full text |Cite
|
Sign up to set email alerts
|

MHC class II presentation of endogenously expressed antigens by transfected dendritic cells

Abstract: Dendritic cells (DC) present immunogenic epitopes of antigens in the context of MHC class I and class II molecules in association with costimulatory molecules, and efficiently activate both cytotoxic T cells and T helper cells. Gene modified DC expressing antigen encoding cDNA represent a particularly attractive approach for the immunotherapy of disease. We previously described a gene delivery system for DC based on receptor-mediated endocytosis of ligand/polyethylenimine (PEI) DNA transfer complexes that targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 47 publications
3
88
2
Order By: Relevance
“…In these assays, macrophages transfected with constructs designed to secrete OVA were best for activating the DO11.10-GFP hybridoma, thus exogenous Ag may enter the MHC class II-processing pathway more efficiently than other Ag forms. Studies by others have also demonstrated the differing abilities of OVA targeted to different cellular locations of transfected DCs to stimulate proliferation of CD4 ϩ DO11.10 T cells (40). In these experiments, OVA targeted to the cell surface using the same TfR fusion construct used in our experiments, or as a fusion with murine invariant chain stimulated proliferation of T cells, whereas cytosolic Ag expression was ineffectual.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In these assays, macrophages transfected with constructs designed to secrete OVA were best for activating the DO11.10-GFP hybridoma, thus exogenous Ag may enter the MHC class II-processing pathway more efficiently than other Ag forms. Studies by others have also demonstrated the differing abilities of OVA targeted to different cellular locations of transfected DCs to stimulate proliferation of CD4 ϩ DO11.10 T cells (40). In these experiments, OVA targeted to the cell surface using the same TfR fusion construct used in our experiments, or as a fusion with murine invariant chain stimulated proliferation of T cells, whereas cytosolic Ag expression was ineffectual.…”
Section: Discussionmentioning
confidence: 62%
“…OVA expressed using this construct is secreted in mammalian cells (17). A plasmid expressing the transmembrane region of the human transferrin receptor (TfR) fused to aa 149 -385 from native OVA (plasmid expressing transferrin-OVA fusion protein; pTfROVA) has been described previously (39,40) and was kindly donated by M. Zenke (Max-Delbück-Center for Molecular Medicine, Berlin, Germany). This construct has been shown by others to target OVA expression to the surface of mammalian cells in vitro and in vivo (39,41).…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…1 The primary advantage of a gene-based vaccination strategy using DCs transduced with the entire TAA gene is that the DCs will present multiple epitopes, including unknown epitopes associated with different MHC Class I molecules, in addition to helper epitopes associated with MHC Class II molecules. 23,24 Our study demonstrated that an adenovirus vector encoding the TAA gene, hgp100, can be used to effectively transfer and express the transgene in iPSDCs. On the other hand, it is generally accepted that iPS cells exhibit high efficiency and simplicity of transgene transfection using electroporation.…”
Section: Discussionmentioning
confidence: 74%
“…Holst et al, 2008). A previous in vitro study (Diebold et al, 2001) revealed that a construct coding for Ii chain fused to a model antigen stimulated MHC class II-restricted but also class Irestricted T cells; furthermore, MHC class I presentation was more efficient. The present results seem to be in line with these observations, extending those results to the in vivo situation.…”
Section: Resultsmentioning
confidence: 99%